PENGARUH MODEL PEMBELAJARAN SCRAMBLE BERBANTUAN MEDIA SMART BOX TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI IPS SMA NEGERI 10 PEKANBARU - Azzahra Putri, Oktarisa; Isjoni, Isjoni; Ananda Hasibuan, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether or not there is an effect of the application of the scramble model and smart box media on the history learning outcomes of class XI IPS students at SMA Negeri 10 Pekanbaru. The approach used in this study is a quantitative approach. The type of research used is a quasi-experimental study (quasi-experimental) with a nonequivalent control group design. The sample used was class XI IPS 2 students as the experimental class and class XI IPS 1 students as the control class. The results of the t-test analysis obtained a sig value of 0.001 > 0.05, so Ha is accepted, namely there is an effect of the application of the scramble learning model assisted by smartbox media on the history learning outcomes of class XI IPS students at SMA Negeri 10 Pekanbaru. The results of the N-Gain test analysis obtained an N-Gain Score of 0.5870 and an N-Gain Percent of 58.69%, which means that the application of the scramble learning model assisted by smartbox media has moderate effectiveness and is quite effective in improving the history learning outcomes of class XI IPS students at SMA Negeri 10 Pekanbaru.